Reporting Avian Influenza surveillance. (29th November 2018) - ,; Brouwer, Adam; Huneau, Adeline; Kuiken, Thijs; Staubach, Christoph; Stegeman, Arjan; Baldinelli, Francesca; Verdonck, Frank; Aznar, Inma
Abstract: Avian influenza viruses infect domestic poultry and wild birds as well as humans. In poultry, depending on whether these viruses are of high pathogenicity (HPAI) or low pathogenicity (LPAI), the infection can cause different clinical signs, with HPAI causing high mortality in poultry flocks. In order to ensure early detection of avian influenza viruses, surveillance in poultry and wild birds is considered essential. In 2010, the European Commission provided some guidelines to Member States (MSs) on how this surveillance should be carried out, both in poultry and wild birds. EFSA received a mandate from the Commission to collate, validate, analyse, and summarise in an annual report the data resulting from the ongoing avian influenza surveillance programmes established in the different MSs. To deliver on this mandate, EFSA, in collaboration with the Standing Working Group on AI, initiated its activities with the drafting of a scientific report where the future vision of this collection framework was presented. Initial and later drafts of this report were shared with MS representatives in order to get feedback on the practicalities concerning the collection and submission of avian influenza surveillance data to EFSA. In the present report, the data that MSs are legally requested to submit to EFSA ('mandatory') and also the data that would be important to collect in order to optimise the outputs ('desirable') are described. A number of actions that would lead to the optimal data collection are also presented and the added value to MSs is discussed. A step‐by‐step implementation of the outlined actions is anticipated, with a description of the initial collection framework for 2019 being included in this report.